The Influence of Using the Power Point Media Trigger Feature on the Learning Motivation of Class VIII Students at SMP Negeri 3 Tolitoli - Ikbal, Ikbal; Saugadi, Saugadi (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Motivation is one of the things that influences student learning success. Without motivation, the learning process will be difficult to achieve success. This research aims to determine the effect of using the Trigger feature of Power Point media on the learning motivation of class VIII students at SMP Negeri 3 Tolitoli. This researcher used a type of quantitative research. The method used in this research was the Pre Experiment or experimental research method, the research subjects were students at SMP Negeri 3 Tolitoli class VIII. The instruments in this research are observation, questionnaires and documentation. As for the results of this research, there is a positive and significant influence. Based on the data that has been collected and tests that have been carried out using product moment correlation from the Statistical Product and Service Solution (SPSS) program, the average calculated R value is R Table based on test results significance 0.5. The correlation coefficient value (calculated r) for each variable shows that the correlation value between the item scores and the total item score for the 6 questions has a correlation value that is greater than the correlation value of the r table at a significance level of 0.05 with degrees of freedom df (N-K)/30-2 =28). So the results can be concluded that there is a difference in the average results of student learning motivation between the learning model using power point media with trigger features and the conventional model.